Gender and spoken language use in consumer finance - Cwynar Andrzej; Porzak Robert; Nowak Paweł; Cwynar Magdalena (Financial Internet Quarterly)
Finance is still stereotypically perceived as a male domain, and social group divisions have linguistic consequences. This study examines whether language use in consumer finance exhibits gendered characteristics by identifying linguistic patterns used by non-expert women and men in this domain. To this end, we analyzed a corpus of spoken language collected through focus group interviews with 36 consumers of both genders, representing a full socio-demographic cross-section. The linguistic analysis was conducted using the Quanteda package in R, as well as tools from generative grammar, textology, ethnolinguistics, and cognitive linguistics. Additionally, respondents’ statements were categorized into speech acts: assertions, directives, commissives, expressives, and constatives. Our findings indicate that while gender differences in language use are subtle, they are nonetheless distinct. Women’s language tends to be more colloquial, descriptive, relational, figurative, and experience-oriented, often carrying greater emotional load. In contrast, men’s language is more professional (or stylized as such), argumentative, factual, and informational, emphasizing a sense of expertise, agency, and self-efficacy. These findings contribute to a deeper understanding of gendered communication patterns in financial discourse.